Taking the Evolution of the Standards of Proof for a Criminal Conviction Seriously - Jacopo Della Torre (Quaestio Facti)
The article offers a diachronic and comparative analysis of different standards of proof for a criminal conviction. The first part focuses on the attempt of medieval and early modern Roman-canon systems to clarify this type of rule through a network of legal proofs. The second part analyses the origins of the main standards for a criminal conviction used today: moral certainty, beyond reasonable doubt and intime conviction. The final part looks to the future, asking whether traditional decision-making criteria should be maintained or replaced by new ones based on the principles of contemporary epistemology.